(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The paper reports a study, which was carried out to examine thermal and frost resistance properties of foamed concrete (FC) with porous aggregate (expanded glass (EG) granules and cenospheres). By adding lightweight and porous aggregate to the FC mixture, it is possible to improve important physical, mechanical, and thermal properties of the prepared FC specimens. In the framework of this study the coefficient of thermal conductivity and frost resistance of hardened FC samples were determined. The structure of FC matrix and used aggregates were characterised by using a method of optical microscopy.